Interfacial shearing behavior along xanthan gum biopolymer-treated sand and solid interfaces and its meaning in geotechnical engineering aspects - Lee, Minhyeong; Im, Jooyoung; Cho, Gye Chun; Ryu, Hee Hwan; Chang, Ilhan (Applied Sciences (Switzerland), 2021)
Recently, environment-friendly microbial biopolymer has been widely applied as a new construction material in geotechnical engineering practices including soil stabilization, slope protec-tion, and ground injection. Biopolymer is known to exhibit substantial improvements in geotechnical properties, such as shear strength enhancement and hydraulic conductivity reduction, through the formation of direct ionic bonds with soil particles, especially clay particles. Moreover, the rheologi-cal characteristics (e.g., pseudoplasticity, shear-rate dependent thixotropy) of biopolymers render distinctive behaviors such as shear thinning and lubrication effect under a high strain condition, while recovering their viscosities and shear stiffnesses when they are at rest. To ensure the practical applicability of biopolymer-based soil treatment, it is important to understand the interfacial inter-action (i.e., friction) between biopolymer-treated soil and adjoining structural members which can be constructed in a biopolymer-treated ground. Thus, in this paper, interfacial shearing behavior of biopolymer-treated soil along solid surfaces as well as internal shearing on biopolymer-soil matrix were explored via direct and interface shear test. Experimental results show a predominant effect of the soil moisture content on the interfacial shear behavior of biopolymer-treated soil which attributes to the rheology transition of biopolymer hydrogels. At low moisture content, condensed biopolymer biofilm mobilizes strong intergranular bonding, where the interfacial shear mainly depends on the physical condition along the surface including the asperity angle. In contrast, the biopolymer induced intergranular bonding weakens as moisture content increases, where most interfacial failures occur in biopolymer-treated soil itself, regardless of the interface condition. In short, this study provides an overall trend of the interfacial friction angle and adhesion variations of xanthan gum biopolymer-treated sand which could be referred when considering a subsequent structural member construction after a biopolymer-based ground improvement practice in field.
Keywords: Biopolymer; Interface; Interface friction angle; Shear strength; Soil–structure; Xanthan gum